2000
DOI: 10.1177/074193250002100405
|View full text |Cite
|
Sign up to set email alerts
|

Personal Experiences and Adjustment of Dutch Adults with Dyslexia

Abstract: Twenty-seven Dutch adults (ages 20-39) with dyslexia participated in individual in-depth interviews about the way they coped with their life and their disability. The interviews were transcribed verbatim and qualitatively and quantitatively analyzed. Most participants felt a strong impact of the dyslexia on daily life and experienced many educational and career problems. School memories were mostly negative, but family relations were predominantly felt as positive and supportive. Parent-school cooperation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
149
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(170 citation statements)
references
References 11 publications
15
149
0
6
Order By: Relevance
“…They had positively reframed their dyslexia and were consciously able to utilize it in their employment (Article I). These findings support a number of other studies that have demonstrated that people who develop positive self-perceptions related to being an individual with dyslexia support their general well-being and employment outcomes (Armstrong & Humphrey, 2009;Burden, 2005;Gerber et al, 1992;Gerber et al, 1996;Hellendoorn & Ruijssenaars, 2000;Ingesson, 2007;McNulty, 2003;Pollak, 2005).…”
Section: Resources For Professional Identity Negotiationsupporting
confidence: 79%
See 1 more Smart Citation
“…They had positively reframed their dyslexia and were consciously able to utilize it in their employment (Article I). These findings support a number of other studies that have demonstrated that people who develop positive self-perceptions related to being an individual with dyslexia support their general well-being and employment outcomes (Armstrong & Humphrey, 2009;Burden, 2005;Gerber et al, 1992;Gerber et al, 1996;Hellendoorn & Ruijssenaars, 2000;Ingesson, 2007;McNulty, 2003;Pollak, 2005).…”
Section: Resources For Professional Identity Negotiationsupporting
confidence: 79%
“…These findings are in line with a number of other investigations that have documented adults with dyslexia being able to develop ingenious strategies to overcome their difficulties (Everatt, Steffert & Smythe, 1999;Gerber et al, 1992;Goldberg et al, 2003;Hellendoorn & Ruijssenaars, 2000;Logan, 2009;McNulty, 2003;Paananen, 2006). In keeping with other published research on practicing teachers with LDs (Ferri et al, 2001;Riddick, 2003;Vogel et al, 2007;Vogel & Sharoni, 2011), compensatory strategies have been confirmed to be of utmost importance for teachers with LD to be successful in their work.…”
Section: Resources For Professional Identity Negotiationsupporting
confidence: 78%
“…There is also evidence that dyslexic adults have lower self-esteem in educational contexts (Carroll and Iles 2006;Madriaga 2007;Riddick et al 1999), and often have to manage memories of very challenging experiences at school which continue to impact upon their adult educational experiences (for example , Madriaga 2007;Mcnulty 2003). Some of these students also seem to find a lack of understanding of the difficulties they face (for example, riddick 2003); or they experience social discomfort in relation to dyslexia (for example, Hellendoorn and Ruijssenaars 2000).…”
Section: Introduction and Literaturementioning
confidence: 99%
“…Hellendoorn and Ruijssenaars (2000) found that most of their participants received less support and understanding in their secondary schools than they did in primary. But in Eleni's research there was little or no support or care practices across the age groups.…”
Section: Care-less Spacesmentioning
confidence: 99%
“…This is especially valuable when institutional care-less-ness is evident. In some cases, parents are the only ones caring for their children and fighting for their wellbeing (Hellendoorn and Ruijssenaars 2000). When institutional caring is insufficient, parents take schooling into their home by offering the materials and tutors their children need (Buswell Griffiths et al 2004).…”
Section: Battling With Professionals -Parental Caringmentioning
confidence: 99%